Digital marketing strategies for fashion and luxury brands - Ozuem, Wilson, 1974-; Azemi, Yllka, 1988- (IGI Global, 2018)
"This book focuses on qualitative discussions on issues related to digital marketing in the Luxury fashion brands. It addresses the relationship between computer-mediated marketing environments and luxury fashion brands. The advert of internet technologies along with its prototypical subsets are turning consumers to digital universe"- Resumé vydavatel
Keywords: internetový marketing; luxusní zboží; módní průmysl; Internet marketing; luxuries; fashion industry; elektronické knihy; sborníky; electronic books; papers of several authors